England’s “Bloody Code” in Crisis and Transition: Executions at the Old Bailey, 1760–1837 - Devereaux, Simon (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2013)
The most celebrated and influential history of execution in England, V.A.C. Gatrell’s The Hanging Tree (Oxford, 1994), uses a survey of execution rates to make two very striking and seemingly persuasive assertions. First, more people were being hanged in early nineteenth-century England than at any time since the early modern era; and second, that the end of capital punishment came far more suddenly than previous studies have recognized. This article acknowledges and extends the importance of Gatrell’s first insight, while arguing that he nevertheless both understates the complexity of developments and overstates the suddenness with which both the letter and the practice of capital punishment were abandoned. It does so through a careful recalculation and analysis of execution rates at London’s Old Bailey courthouse, where execution was practiced on a far larger scale than in any other jurisdiction in the Anglo-American world, and whose practice most profoundly shaped the perceptions of both critics and proponents of capital punishment alike.